Corporate social responsibility disclosure : a study of Malaysian largest companies - Mohamad Mokhlis bin Ahmad Fuad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The idea of corporate social responsibility which was introduced in the early 1920s has become an integral part of business nowadays. In Malaysia, Bursa Malaysia has introduced the Bursa Malaysia CSR framework in 2006 to promote better CSR disclosure in Malaysian public listed companies' annual reports. On top of that, the year 2006 also witnessed the introduction of the Silver Book, an additional CSR disclosure guideline for the Malaysian Government-Linked Companies (GLCs). Pursuant to these new milestones in Malaysian CSR practice, the present study aims to provide an updated analysis on the extent and quality of CSR disclosure among Malaysian largest public listed companies including the GLCs. In addition to that, several firms' characteristics were statistically tested to ascertain their influence on the extent and quality of CSR disclosure. These firms' characteristics are profitability, industry type, multiple listing status, company age, industry competitiveness, and Shari'ah compliance status. The extent and quality of CSR disclosure were discussed in light of the political economy theory and the concept of political visibility. In order to examine the extent and quality of CSR disclosure, content analysis using a CSR disclosure checklist and decision rules adopted from Hackston and Milne (1996) were utilised. The present study also performed statistical analysis in order to analyse the relationships between firms' characteristics and the extent and quality of CSR disclosure. Samples consisted of 100 largest Malaysian public listed companies which include 20 GLCs. Results suggested that all sample companies provide CSR disclosure ranging from 34 to 1,846 number of sentences. Despite that, the quality of CSR disclosure is still low with a high dominance of declarative sentences. Among the six independent variables tested, only industry type and industrial competiveness are influencing CSR disclosure. Overall, the findings provide some support to the political economy theory and the concept of political visibility. Thus, the present study made some contribution to the CSR research, particularly in Malaysia. The present study also provides some indicator as to the current state of extent and quality of CSR disclosure in Malaysia. Future researchers are proposed to embark on a longitudinal analysis on CSR disclosure. In methodological aspect, future researchers are suggested to perform a triangulation research method in order to gain a more in-depth understanding on the extent and quality of CSR disclosure.